A prediction model for the efficacy of continuous positive airway pressure on bronchiolitis - Shi, Qingxia; Zhao, Zhihua; Lin, Jilei; Zhang, Yin; Dai, Jihong (Frontiers in Pediatrics, 2022)
Objectives: Prediction of the efficacy of continuous positive airway pressure (CPAP) on bronchiolitis is necessary for timely treatment. This study aims to establish a nomogram for efficacy of CPAP on bronchiolitis, and compares accuracy with Pediatric Risk of Mortality III (PRISM III), Brighton Pediatric Early Warning Score (Brighton PEWS) and Pediatric Critical Illness Score (PCIS). Methods: From February 2014 to December 2020, data on children diagnosed with bronchiolitis and treated with CPAP in Chongqing was collected. The nomogram was evaluated by using multivariate logistic regression analysis. We compared the predictive value of model with PRISM III, PEWS and PCIS. Results: A total of 510 children were included. The nomogram prediction model including fever, APTT, white blood cells, serum potassium concentration, lactic acid, immunodeficiency, atelectasis, lung consolidation, congenital airway dysplasia and congenital heart disease was established. The AUC of the nomogram was 0.919 in the training set and 0.947 in the validating set. The model fitted well, as evidenced by the calibration curve and Hosmer-Lemeshow goodness-of-fit test. We discovered that the nomogram significantly performed better than PRISM III, PCIS and PEWS. Conclusions: A nomogram including ten factors for predicting the efficacy of CPAP on bronchiolitis was established. It had higher performance than the PRISM Ⅲ, PCIS, and PEWS in terms of clinical benefits.